Effects of nociceptin/orphanin FQ on rats with cathartic colon - Li, Hai-Yan (Baishideng Publishing Group Co., Limited, 2007)
AIM: To demonstrate the change and effect of nociceptin/orphanin FQ in the colon of rats with cathartic colon. METHODS: The cathartic colon model was established by feeding rats rhubarb for 3 mo, the changes of colonic electromyography were investigated by both suspension muscle strips test and serosal recordings of colonic myoelectrical activity. Immunohistochemical staining (S-P methods) and image analysis were used to determine the changes of nociceptin/orphanin FQ in the proximal colon and distal colon of rats with cathartic colon. RESULTS: Suspension muscle strips test in vitro showed OFQ (10(-9)-10(-6) mol/L) concentration dependently caused an immediate tonic contraction in the isolated colon. But the increase of tension in cathartic colon was less than control groups (P < 0.01). Intravenous administration of OFQ (1 μg/kg) caused phasic contractions in the proximal colon, while the amplitude of phasic contractions caused by OFQ in cathartic colon was much lower than that in the control groups (2.58 ± 0.41 vs 4.16 ± 0.53, t = -2.6, P = 0.012). OFQ was highly expressed in the myenteric plexus of the rat colon but not in the muscle cells. The immunoreactivity of OFQ in the proximal colon in cathartic colon rats decreased significantly compared with the control group (P = 0.001). CONCLUSION: Colonic smooth muscle of cathartic colon showed low sensitivity to the stimulation of OFQ, suggesting that it might be caused by the abnormal distribution of OFQ or the abnormalities of receptors, leading to the disorganization of dynamic and incoordinated contractions.